Casting a Shadow : Productivity of Formal Firms and Informality - Amin, Mohammad; Ohnsorge, Franziska L.; Okou, Cedric (World Bank, Washington, DC, 2019)
Using firm-level survey data for a large cross section of countries, the paper assesses the gap in labor productivity between formal and informal firms in developing countries for which comparable data are available. It also investigates the impact of competition from informal firms on the labor productivity of formal firms. The results show that on average, the labor productivity of informal firms is about one-fourth that of formal firms. Moreover, the labor productivity of formal firms that face competition from informal firms is about 75 percent of the average labor productivity of formal firms that do not experience informal competition. This suggests that competition from the informal sector can erode formal firms' market share and the resources available to boost productivity where formal firms shoulder the additional cost of regulatory compliance. These findings are robust to a range of firm and country characteristics as well as checks for endogeneity concerns.